A flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings

Through a multi-step flotation process, PPM-grade low-iron sand is extracted and prepared from slate engineering slag tailings, solving the problem of difficulty in effectively slate tailings in the prior art, and achieving efficient quartz sand purification and recycling.

CN115283130BActive Publication Date: 2025-04-18XIAMEN XINYISHENG NONMETAL MATERIAL SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210914364.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-01
Publication Date
2025-04-18
Estimated Expiration
2042-08-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use slate engineering slag tailings to prepare low-iron quartz sand, especially in the flotation method, which lacks efficient solutions.

Method used

A flotation process is adopted, including crushing the engineering slag to a suitable particle size, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate for the first set of flotation, followed by grinding and passing through magnetic separation, second set of flotation and acid leaching, to finally obtain PPM grade low iron sand.

Benefits of technology

Through this process, the SiO2 content and recovery rate in slate tailings are significantly improved, production costs are reduced, and the iron impurity content in concentrates is effectively reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of quartz sand preparation, and in particular to a flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings, comprising the following steps: crushing the engineering slag to a particle size of less than 0.45 mm to obtain primary crushed material; mixing the primary crushed material with water to obtain a mixture, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate to the mixture, and obtaining roughing tailings through a first group of flotation; grinding the roughing tailings to a particle size of less than 0.08 mm, removing fine mud through a hydraulic classifier, and obtaining a sedimentation material after desludging; subjecting the sedimentation material to magnetic separation, a second group of flotation, and acid leaching to obtain PPM-grade low-iron sand. The present invention adopts the processing procedures of material layered product extraction and special collector selection, and the process method is simple, easy to operate, and has the characteristics of low cost, easy availability of raw materials, and low energy consumption, providing a new way to prepare high-purity low-iron quartz powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of quartz sand preparation, and in particular to a flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings. Background Art

[0002] Quartz sand is a hard, wear-resistant, chemically stable silicate mineral, the main chemical component of which is SiO2. The unique physical and chemical properties of quartz sand make it widely used in traditional industries such as casting, metallurgy, rubber, abrasives, ceramics, and construction. As a mineral rich in SiO2, slate is very abundant in my country and is a commonly used building stone. Its finished products are widely used in the construction industry as decorative materials, and are widely used as floors, exterior walls, eaves and tiles of urban public buildings. However, the mining yield of slate is only about 10%, and more than 85% of engineering slag and waste tailings will be generated during the mining and processing process. These engineering slag tailings are generally transported to cement plants or backfilled, with low economic benefits. The main components of slate slag are SiO2, Al2O3, Fe2O3, MgO, etc., and the quartz content of 55-65% makes it possible to obtain high-purity quartz sand through deep processing.

[0003] As a sedimentary rock, slate minerals are composed of fine particles, more matrix and cement, and often contain high-iron components such as mica and chlorite, making it difficult to purify the ore. Although the iron content of the selected materials has been significantly reduced by the universal scrubbing and magnetic separation methods, it is still not enough to obtain satisfactory concentrate indicators. Therefore, a more directional flotation process becomes the key to achieving the purification requirements.

[0004] There is no report on the use of slate engineering slag tailings to prepare low-iron quartz sand, especially in the flotation method. Therefore, the present invention provides a flotation process capable of extracting and preparing PPM-level low-iron sand from slate urban engineering slag tailings. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the present application provides a flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings.

[0006] The present application provides a flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings, which adopts the following technical solution:

[0007] A flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings comprises the following steps:

[0008] (1) crushing the engineering slag to a particle size of less than 0.45 mm to obtain primary crushed material;

[0009] (2) mixing the primary crushed material with water to obtain a mixture, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate to the mixture, and performing a first group of flotation to obtain a rough tailing;

[0010] (3) grinding the roughing tailings to a particle size of less than 0.08 mm, removing fine mud through a hydraulic classifier, and obtaining a desludified sediment material;

[0011] (4) The sedimentation material is subjected to magnetic separation, second group flotation, and acid leaching to obtain PPM-grade low iron sand.

[0012] Preferably, the amounts of the alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate are 550-900 g / t, 400-700 g / t and 300-500 g / t respectively.

[0013] Preferably, the mass ratio of the alkyl primary amine acetate to the sodium petroleum sulfonate is 1-1.5:1.

[0014] Preferably, the pH value of the first group during flotation is 7-10.

[0015] Preferably, the first group of flotation adopts aeration flotation, and the aeration volume is not less than 30m3 / m2·h.

[0016] Preferably, the mass concentration of the pulp during the first group of flotation is 30-45%.

[0017] Preferably, the second group of flotation steps includes a first stage flotation, a second stage flotation and a third stage flotation;

[0018] (1) In the first stage of flotation, hydrochloric acid is used as a regulator and fatty acid collectors are used to reverse float out iron-containing minerals at pH = 4.0-5.0;

[0019] (2) In the second stage of flotation, sodium petroleum sulfonate and diamines are used as collectors to reverse float feldspar minerals at pH = 2.0-3.0;

[0020] (3) In the third flotation, sodium hydroxide is used as a regulator, tallow propylene diamine and sodium dodecyl polyoxyethylene ether sulfate are used as collectors, and sodium silicate and calcium chloride are used as auxiliary agents. At pH = 8.0-10.0, layered aluminum silicate minerals are reversely floated out.

[0021] Preferably, the usage ratio of the tallow trimethylene diamine to sodium dodecyl polyoxyethylene ether sulfate is 1:0.1-1.

[0022] Preferably, the magnetic separation adopts high-gradient magnetic separation, and the sedimentation material is magnetically separated at a magnetic field strength of 10,000-12,000 GS.

[0023] Preferably, the acid leaching step is to immerse the sedimentation material in an oxalic acid solution having a concentration of 10-15%, ultrasonically stir at room temperature for 4-5 hours, and finally wash with deionized water until neutral.

[0024] By adopting the above technical solution, the slate engineering slag tailings are recycled and reused, turning waste into treasure and preparing PPM-grade low-iron sand with higher added value.

[0025] In summary, the present application includes at least one of the following beneficial technical effects:

[0026] 1. The present invention uses engineering slag tailings as raw materials, firstly floats low-grade slag tailings to improve their grade through a first-stage grinding process, effectively improves the SiO2 content in the slag tailings, reduces the ineffective energy consumption of gangue minerals in the second-stage grinding process, and can obtain more finished concentrates under the same energy consumption, thereby reducing the production cost.

[0027] 2. The present invention finds that when alkyl primary amine acetates and sodium petroleum sulfonate are used in combination, they have strong floatability for large-particle materials in slate. When the particle size is large and the dissociation is insufficient, the auxiliary use of sodium hexametaphosphate can form the flotation separation of SiO2 and other components in the large-particle slate, so that the SiO2 content in the flotation tailings is significantly increased. When the SiO2 content of the original ore is 59%, the tailings can be 78% and the recovery rate can be 58%, which is a good indicator, thereby realizing flotation purification under large particle size.

[0028] 3. The present invention adopts a combined collector of tallow propanediamine and sodium dodecyl polyoxyethylene ether sulfate according to the composition structure of slate. Compared with a single collector, the synergistic effect and synergistic effect produced by the combination of tallow propanediamine and sodium dodecyl polyoxyethylene ether sulfate have a stronger flotation selectivity for layered aluminum silicate minerals such as iron-containing chlorite in slate, thereby reducing the iron impurity content in the concentrate.

[0029] 4. The present invention adopts the processing steps of material layered extraction and specially selected collectors. The process method is simple, easy to operate, low cost, easy to obtain raw materials, and low energy consumption. It provides a new way to prepare high-purity low-iron quartz powder. DETAILED DESCRIPTION

[0030] In order to better understand the present invention, the content of the present invention is further clearly described below in conjunction with the embodiments, but the protection content of the present invention is not limited to the following embodiments. In the following description, a large number of specific details are given in order to provide a more thorough understanding of the present invention.

[0031] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0032] The composition and content of the slate engineering slag tailings in the following examples are roughly as follows (%):

[0033] SiO2 Al2O3 Fe2O3 CaO TiO2 MgO K2O Na2O 59.94 17.86 11.62 1.03 1.1 1.52 2.48 0.48

[0034] The main crushing equipment used are: gyratory crusher (PXZ62-75), compound crusher (PFL-1000), wet ball mill (Ф2800).

[0035] Example 1

[0036] A flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings comprises the following steps:

[0037] (1) crushing the engineering slag to a particle size of less than 0.45 mm to obtain primary crushed material;

[0038] (2) Mixing the primary crushed material with water and stirring to obtain a mixture, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate to the mixture, and performing the first group of flotation at a pH value of 7-8 to obtain rough tailings. The first group of flotation uses an aeration volume of 30m 3 / m 2 h of aeration flotation, the mass concentration of the ore pulp is 35%; the dosages of alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate are 600g / t, 450g / t and 400g / t respectively. Alkyl primary amine acetate is FLOTIGAM TM 7500. The first group of flotation obtained 76% SiO2 content and 11% Al2O3 content in the rougher tailings, and 58% SiO2 content and 32% Al2O3 content in the scraping product.

[0039] (3) grinding the roughing tailings to a particle size of less than 0.08 mm, removing fine mud through a hydraulic classifier, and obtaining a desludified sediment material;

[0040] (4) subjecting the sedimented material to high-gradient magnetic separation at a magnetic field strength of 10,000 to 12,000 GS;

[0041] (5) subjecting the magnetically separated material to a second group of flotation, the second group of flotation specifically comprising the following steps: placing the magnetically separated material into a flotation machine for a first stage of flotation, adding a fatty acid collector and adjusting the pH to 4.0-5.0 with hydrochloric acid, reversely flotating out the iron-containing minerals to obtain the first stage of flotation tailings; the fatty acid collector is a saponified product of stearic acid.

[0042] The first stage flotation tailings were washed with deionized water until neutral and placed in a flotation machine for the second stage flotation. First, 800 g / t of sodium petroleum sulfonate was added. After sufficient stirring, 450 g / t of dodecylamine hydrochloride was added. The pH was then adjusted to 2.0-3.0 with hydrochloric acid, and feldspar minerals were reversely floated to obtain the second stage flotation tailings.

[0043] The second stage flotation tailings were washed with deionized water until neutral and placed in a flotation machine for the third stage flotation. After adding 500 g / t of sodium silicate, 300 g / t of calcium chloride, 750 g / t of tallow propylene diamine and 200 g / t of sodium dodecyl polyoxyethylene ether sulfate, the pH was adjusted to 8 with sodium hydroxide. The flotation time was 3 to 5 minutes, and the layered aluminum silicate minerals were reversely floated to obtain the third stage flotation tailings.

[0044] (6) The tailings from the third flotation stage are immersed in an oxalic acid solution containing a concentration of 10-15%, and ultrasonically stirred at room temperature for 4-5 hours. Finally, the tailings are washed with deionized water until neutral, dried, and cooled to room temperature to obtain quartz concentrate.

[0045] Example 2

[0046] A flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings comprises the following steps:

[0047] (1) crushing the engineering slag to a particle size of less than 0.45 mm to obtain primary crushed material;

[0048] (2) Mixing the primary crushed material with water and stirring to obtain a mixture, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate to the mixture, and performing the first group of flotation at a pH value of 7-8 to obtain rough tailings. The first group of flotation uses an aeration volume of 30m 3 / m 2 h of aeration flotation, the mass concentration of the ore pulp is 40%; the dosages of alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate are 800g / t, 550g / t and 300g / t respectively. Alkyl primary amine acetate is FLOTIGAM produced by CLARIANT TM 7500. The first group of flotation obtained SiO2 content of 77% and Al2O3 content of 10% in the rougher tailings, and SiO2 content of 61% and Al2O3 content of 29% in the scraping product.

[0049] (3) grinding the roughing tailings to a particle size of less than 0.08 mm, removing fine mud through a hydraulic classifier, and obtaining a desludified sediment material;

[0050] (4) subjecting the sedimented material to high-gradient magnetic separation at a magnetic field strength of 10,000 to 12,000 GS;

[0051] (5) subjecting the magnetically separated material to a second group of flotation, the second group of flotation specifically comprising the following steps: placing the magnetically separated material into a flotation machine for a first stage of flotation, adding a fatty acid collector and adjusting the pH to 4.0-5.0 with hydrochloric acid, reversely flotating out the iron-containing minerals to obtain the first stage of flotation tailings; the fatty acid collector is a saponification product of oleic acid.

[0052] The first stage flotation tailings were washed with deionized water until neutral and placed in a flotation machine for the second stage flotation. First, 900 g / t of sodium petroleum sulfonate was added. After sufficient stirring, 600 g / t of dodecylamine hydrochloride was added. The pH was then adjusted to 2.0-3.0 with hydrochloric acid, and feldspar minerals were reversely floated to obtain the second stage flotation tailings.

[0053] The second stage flotation tailings were washed with deionized water until neutral and placed in a flotation machine for the third stage flotation. After adding 600 g / t of sodium silicate, 500 g / t of calcium chloride, 850 g / t of tallow propylene diamine and 550 g / t of sodium dodecyl polyoxyethylene ether sulfate, the pH was adjusted to 9 with sodium hydroxide. The flotation time was 3 to 5 minutes, and the layered aluminum silicate minerals were reversely floated to obtain the third stage flotation tailings.

[0054] (6) The tailings from the third flotation stage are immersed in an oxalic acid solution containing a concentration of 10-15%, and ultrasonically stirred at room temperature for 4-5 hours. Finally, the tailings are washed with deionized water until neutral, dried, and cooled to room temperature to obtain quartz concentrate.

[0055] Example 3

[0056] A flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings comprises the following steps:

[0057] (1) crushing the engineering slag to a particle size of less than 0.45 mm to obtain primary crushed material;

[0058] (2) Mixing the primary crushed material with water and stirring to obtain a mixture, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate to the mixture, and performing the first group of flotation at a pH value of 9-10 to obtain rough tailings. The first group of flotation uses an aeration volume of 40m 3 / m 2h of aeration flotation, the mass concentration of the ore pulp is 45%; the dosages of alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate are 900 g / t, 700 g / t and 500 g / t respectively. Alkyl primary amine acetate is FLOTIGAM produced by CLARIANT TM 7500. The first group of flotation obtained SiO2 content of 78% and Al2O3 content of 9% in rougher tailings, and SiO2 content of 62% and Al2O3 content of 27% in scraping products.

[0059] (3) grinding the roughing tailings to a particle size of less than 0.08 mm, removing fine mud through a hydraulic classifier, and obtaining a desludified sediment material;

[0060] (4) subjecting the sedimented material to high-gradient magnetic separation at a magnetic field strength of 10,000 to 12,000 GS;

[0061] (5) subjecting the magnetically separated material to a second group of flotation, the second group of flotation specifically comprising the following steps: placing the magnetically separated material into a flotation machine for a first stage of flotation, adding a fatty acid collector and adjusting the pH to 4.0-5.0 with hydrochloric acid, reversely flotating out the iron-containing minerals to obtain the first stage of flotation tailings; the fatty acid collector is a saponified product of stearic acid.

[0062] The first stage flotation tailings were washed with deionized water until neutral and placed in a flotation machine for the second stage flotation. First, 800 g / t of sodium petroleum sulfonate was added. After sufficient stirring, 450 g / t of dodecylamine hydrochloride was added. The pH was then adjusted to 2.0-3.0 with hydrochloric acid, and feldspar minerals were reversely floated to obtain the second stage flotation tailings.

[0063] The second stage flotation tailings were washed with deionized water until neutral and placed in a flotation machine for the third stage flotation. After adding 600 g / t of sodium silicate, 450 g / t of calcium chloride, 850 g / t of tallow propylene diamine and 600 g / t of sodium dodecyl polyoxyethylene ether sulfate, the pH was adjusted to 8 with sodium hydroxide. The flotation time was 3 to 5 minutes, and the layered aluminum silicate minerals were reversely floated to obtain the third stage flotation tailings.

[0064] (6) The tailings from the third flotation stage are immersed in an oxalic acid solution containing a concentration of 10-15%, and ultrasonically stirred at room temperature for 4-5 hours. Finally, the tailings are washed with deionized water until neutral, dried, and cooled to room temperature to obtain quartz concentrate.

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the rougher tailings are no longer ground, and the rest is the same as Example 1.

[0067] Comparative Example 2

[0068] The only difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the engineering slag is crushed to a particle size of 0.6 mm, and 80% of the particle size of the obtained primary crushed material is greater than 0.45 mm. The rest is the same as Example 1.

[0069] Comparative Example 3

[0070] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the amount of alkyl primary amine acetate used in the first group of flotation is zero, and the rest is the same as Example 1.

[0071] Comparative Example 4

[0072] The only difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, there is no first group of flotation operations, and the rest is the same as Example 1.

[0073] Comparative Example 5

[0074] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the amount of alkyl primary amine acetate used in the first group of flotation is 550 g / t, and the amount of petroleum sodium sulfonate used is 700 g / t, and the rest is the same as Example 1.

[0075] Comparative Example 6

[0076] The difference between Comparative Example 6 and Example 1 is that in Comparative Example 6, the first group of flotation does not use aeration flotation, and the rest is the same as Example 1.

[0077] Comparative Example 7

[0078] The only difference between Comparative Example 7 and Example 1 is that in Comparative Example 7, the amount of calcium chloride used in the third stage of flotation is zero, and the rest is the same as Example 1.

[0079] Comparative Example 8

[0080] The only difference between Comparative Example 8 and Example 1 is that in Comparative Example 8, the amount of sodium dodecyl polyoxyethylene ether sulfate used in the third stage of flotation is zero, and the rest is the same as Example 1.

[0081] Comparative Example 9

[0082] The only difference between Comparative Example 9 and Example 1 is that in Comparative Example 9, the amount of tallow trimethylene diamine used in the third stage flotation is 550 g / t and the amount of sodium dodecyl polyoxyethylene ether sulfate used is 750 g / t, and the rest is the same as Example 1.

[0083] Results: The parameters of the products obtained in Examples 1-3 and Comparative Examples 1-9 were tested, and the specific data are shown in the following table:

[0084] Table 1

[0085]

[0086] The main difference between Example 1 and Comparative Example 4 is that before the material is ground to a fine particle size suitable for flotation, Example 1 first performs a process of pre-purification and grading of the material to enrich the SiO2 in the material. The energy consumption of the grinding operation in the ore dressing plant accounts for about 45%-55% of the total energy consumption of the plant, and the production cost accounts for 40%-60% of the total cost of the ore dressing plant. When obtaining the same quality of quartz concentrate, the energy consumption of Example 1 is 10-20% lower than that of Comparative Example 4, which reduces the production cost.

[0087] Compared with Comparative Example 8, in Comparative Example 8, because sodium dodecyl polyoxyethylene ether sulfate was not added, the iron content in the obtained quartz concentrate was higher. After further testing, it was found that the quartz concentrate contained residual chlorite and other iron-containing impurities. This is because under alkaline conditions, the anionic carboxyl oxygen of sodium dodecyl polyoxyethylene ether sulfate can form a chemical bond with the active metal calcium ion in the hydroxyl complex adsorbed on the surface of chlorite to achieve chemical adsorption. At the same time, the various oxygen atomic structures of sodium dodecyl polyoxyethylene ether sulfate further enhance this targeting effect, so that sodium dodecyl polyoxyethylene ether sulfate has good selectivity for iron-containing impurities such as chlorite in slate. Therefore, the composite sodium dodecyl polyoxyethylene ether sulfate flotation can obtain a lower iron content in the obtained quartz concentrate.

[0088] It should be understood that the specific embodiments described above are only used to explain the present invention, and are not used to limit the present invention. Obvious changes or modifications derived from the spirit of the present invention are still within the protection scope of the present invention.

Claims

1. A flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings, characterized in that The following steps are involved: (1) Crushing the engineering slag to a particle size of less than 0.45 mm to obtain primary crushed material; (2) mixing the primary crushed material with water to obtain a mixture, adding alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate to the mixture, and performing a first group of flotation to obtain a rough tailing; (3) Grinding the roughing tailings to a particle size of less than 0.08 mm, removing fine mud through a hydraulic classifier, and obtaining the desludged sediment material; (4) The sedimented material is subjected to magnetic separation, a second group of flotation and acid leaching in sequence to obtain PPM-grade low-iron sand.

2. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The dosage of the alkyl primary amine acetate, sodium petroleum sulfonate and sodium hexametaphosphate is 550-900 g / t, 400-700 g / t and 300-500 g / t respectively.

3. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 2, characterized in that: The mass ratio of the alkyl primary amine acetate to the sodium petroleum sulfonate is 1-1.5:

1.

4. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The pH value of the first group during flotation is 7-10.

5. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The first group of flotation adopts aeration flotation, and the aeration volume is not less than 30m 3 / m 2 ·h.

6. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The mass concentration of the ore pulp during the first group of flotation is 30-45%.

7. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The second group of flotation steps includes a first stage flotation, a second stage flotation and a third stage flotation; (1) In the first stage of flotation, hydrochloric acid is used as a regulator and fatty acid collectors are used to reverse float out iron-containing minerals at pH = 4.0-5.0; (2) In the second stage of flotation, sodium petroleum sulfonate and diamines are used as collectors to reverse float out feldspar minerals at pH = 2.0-3.0; (3) In the third flotation, sodium hydroxide is used as a regulator, tallow propylene diamine and sodium dodecyl polyoxyethylene ether sulfate are used as collectors, and sodium silicate and calcium chloride are used as auxiliary agents. At pH = 8.0-10.0, layered aluminum silicate minerals are reversely floated out.

8. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 7, characterized in that: The mass ratio of the tallow trimethylene diamine to sodium dodecyl polyoxyethylene ether sulfate is 1:0.1-1.

9. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The magnetic separation adopts high-gradient magnetic separation to carry out magnetic separation on the sedimentation material at a magnetic field strength of 10,000-12,000 GS.

10. The flotation process for preparing PPM-grade low-iron sand from urban engineering slag tailings according to claim 1, characterized in that: The acid leaching step comprises immersing the sedimentation material in an oxalic acid solution containing a concentration of 10-15%, stirring the solution under ultrasonication at room temperature for 4-5 hours, and finally washing the solution with deionized water until the solution is neutral.

Citation Information

Patent Citations

  • Impurity removal process for quartz sand

    CN102189037A

  • Method for producing silica micropowder by utilizing silica sand tailings

    CN107188190A